Kocuria kristinae (Unusual Pathogen) Isolated from Cerebrospinal Fluid: A Case of Acute Meningitis - P. Arun Kumar; R. A. Chougale (Highlights on Medicine and Medical Research Vol. 15, 2021)
Kocuria species are emerging opportunistic pathogens, mostly seen in immunocompromised patients and in patients with severe underlying disease. Nowadays the incidence of different types of Kocuria infections have been reported even though sometimes misidentified as CONS. To confirm them as pathogens by using newer methods like Vitek 2, MALDI-TOF Spectrometry, 16S RNA and repeated specimens have been used. Here, we report a case of acute bacterial meningitis caused by K. kristniae. In this case, the patient had undergone craniotomy. Hence, there is a chance that the cocci may have directly entered during head injury; and could have established the opportunistic infection.